Avoiding the death of the newspaper industry in Indonesia and the transformation of the digital media business - Supadiyanto, Supadiyanto; Murti, Sudaru (Technium Social Sciences Journal, 2024)
The circulation of newspapers in Indonesia has been at its lowest point in the last 10 years. Print media companies have collapsed and closed, and most have shifted to online media businesses. What is the fate of various print outlets and media in Indonesia amidst the death knell of print media business in Indonesia? What is the ultimate strategy to save the print media business in Indonesia and can the business survive until 2030? The paradigm of this research is qualitative. The research took place from January 2023 to December 2024. Data collection techniques were via literature review, observation, and documentation. As a result, the circulation of various print media in Indonesia has decreased drastically by around 1 million copies per year. By the end of 2023, the circulation will be around 5 million copies. The researcher predicts that by 2030, the number of print media companies is estimated to be only 100 companies. Emergency rescue efforts for the print media business through: media transformation, attracting young readers; integration of print media, online media, and social media businesses; and maintaining content according to the needs of customers and potential readers.